Effects of dietary levels of brown seaweeds and plant polyphenols on growth and meat quality parameters in growing rabbit. (March 2020) - Rossi, Raffaella; Vizzarri, Francesco; Chiapparini, Sara; Ratti, Sabrina; Casamassima, Donato; Palazzo, Marisa; Corino, Carlo
Abstract: Growth performances, carcass characteristics and meat quality parameters from growing rabbit fed with two levels of dietary brown seaweed ( Laminaria spp ) and plant polyphenols were investigated. One hundred and forty-four New Zealand White rabbits were allotted into three dietary treatments containing 0 (C), 0.3% (T1), and 0.6% (T2) of brown seaweed and plant polyphenols mixture for 42 days. Growth performances and carcass weight were improved in T1 group. Vitamin A and E content in Longissimus thoracis and lumborum (LTL) and Semimembranosus (SM) muscle were enhanced in the treated groups. In the SM muscle, the oxidative stability was improved in rabbit fed with both dosages of dietary supplement, and the cholesterol content tended to be lower in T1 than in T2 and C groups. The LTL and SM muscle sensory characteristics were improved. In conclusion, dietary integration with a low dosage of brown seaweed and plant polyphenols is a valid strategy for enhance growth performance and produce healthier rabbit meat. Highlights: Supplementation of brown seaweeds and plant polyphenols in growing rabbit was used. Rabbits growth performances was evaluated from weaning to slaughter. Quality parameters of Longissimus lumborum and Semimembranosus muscles was evaluated. The low dosage of dietary supplement positively affects growth parameters. Meat quality parameters are enhanced in meat from rabbit fed natural supplement.